Esthetics of the moment : literature and art in the French Enlightenment - Kavanagh, Thomas M. (Critical authors & issues., 1996)
The literature and art of the French Enlightenment is everywhere marked by an intense awareness of the moment. The parallel projects of living in, representing, and learning from the moment run through the Enlightenment's endeavors as tokens of an ambition and a heritage imposing its only and ultimately impossible cohesion. In this illuminating study, Thomas M. Kavanagh argues that Enlightenment culture and its tensions, contradictions, and achievements flow from a subversive attention to the present as present, freed from the weight of past and future. Examining a wide sweep of literary and artistic culture, Kavanagh argues against the traditional view of the Age of Reason as one of coherent, recognizable ideology expressed in a structured narrative form. In literature, he analyzes the moment at work in the inebriating lightness of Marivaux's repartee; the new-found freedom of Lahontan's and Rousseau's ideals of a consciousness limited to the present; Diderot's championing of Epicurean epistemology; Graffigny's portrayal of abrupt cultural displacement; and Casanova's penchant for chance's redefining moment. The moment in art theory and practice is explored in such forms as de Piles's defense of color; Du Bos's foregrounding of perception; Watteau's indulgence in a corporeal present; Chardin's dismantling of mimesis; and Boucher's and Fragonard's thematics of desire.